EVALUATION OF TRICHODERMA SPP. AGAINST SEED AND SOIL BORNE DISEASES OF GROUNDNUT, SOYBEAN AND SESAMUM UNDER IN VITRO CONDITIONS - P. RAJANIKANTH and SRINIVASA CHARY, S. VIJAYKUMAR, B. RAJESWARI, R. D. PRASAD, K. V. S. P. CHANDRIKA (The Journal of Research, PJTSAU, 2023)
The present study was conducted to evaluate the efficacy of biocontrol agents against stem rot disease in groundnut, charcoal rot disease in soybean and stem and root rot disease of sesame by employing dual culture technique with six isolates of Trichoderma spp. obtained from ICAR-IIOR during the year 2020. The results indicated that T. harzianum (Th4d) was found effective in inhibiting the mycelial growth of S. rolfsii in groundnut (71.9%), M. phaseolina in soybean (67%) and M. phaseolina in sesamum (66%) followed by T. asperellum (TaDOR 7316) isolate inhibited mycelial growth against three test pathogens to an extent of 61.9 per cent, 61.9 per cent and 55.9 per cent, respectively. Least mycelial inhibition was recorded by T. asperellum (Ta10) against groundnut stem rot (42.8%) and soybean charcoal rot (53.7%) followed by T. asperellum (Ta11) in sesamum stem and root rot with 43.3 per cent inhibition. The antagonists T. harzianum (Th4d) showing its efficacy of more than 50 per cent can be utilized as an effective biocontrol agent against test pathogens in three important oilseed crops under field conditions.